PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK UNTUK MELATIH KETERAMPILAN BERPIKIR SISWA PADA TEMA 1 SUBTEMA 1 KELAS V SD - Sinaga, Annisa Irfyanti; Ananda, Lala Jelita (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to produce Big Book learning media that is valid, practical and effective in training students' thinking skills in class V at SDN 091324 Merek Raya. This research is development research that uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this research were class V teachers and class V students at SD Negeri 091324 Merek Raya. The object of research in this study is the validation, practicality and effectiveness of the Big Book learning media in training students' thinking skills. The data collection techniques used are interviews, tests, observation and documentation. The instruments used in data collection were teacher interview instruments, media design and media material validation questionnaires, educational practitioner questionnaires, student response questionnaires, and test questions. The results of the research show that the validation results by media design expert validators obtained an average score of 4.7 with a percentage result of 89% in the "Very Eligible" category and validation results by media material expert validators obtained an average value of 4.3 with a percentage result of 86% œVery Decent category. The practicality test using teacher responses obtained a percentage result of 87% in the "Very Practical" category and the students' responses obtained an average score of 4.59 in the "Very Practical" category. Testing the effectiveness of the media, it can be seen that after using what was developed, students' thinking skills increased from students' thinking skills before using the media, namely 61% in the "Quite Effective" category, increasing to 86% in the "Very Effective" category and the students' average score increased from the initial average. The average before using the media was 61.15 with the "Not Complete" completion criteria increasing to 86.54 with the "Complete" completion criteria.